2001
DOI: 10.1093/aje/154.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time Physical Activity Levels and Changes in Relation to Risk of Hip Fracture in Men and Women

Abstract: The authors prospectively studied the effect of leisure-time physical activity level on hip fracture risk along with the influence of within-subject changes in activity levels, while taking possible confounding by other health behaviors and poor health into account. Analyses were based on pooled data from three population studies conducted in Copenhagen, Denmark. Among 13,183 women and 17,045 men, 1,121 first hip fractures were identified during follow-up. In comparison with being sedentary, the relative risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 33 publications
3
52
2
2
Order By: Relevance
“…Leisure-time physical activity remained a protective factor after adjustment for other factors. Earlier analyses have also found fracture protection from leisure-time physical activity [11,[20][21][22][23][24] and higher BMI [24,25]. To our knowledge, no other studies reported a difference between leisure-time and work activity with regard to the fracture risk.…”
Section: Discussionmentioning
confidence: 52%
“…Leisure-time physical activity remained a protective factor after adjustment for other factors. Earlier analyses have also found fracture protection from leisure-time physical activity [11,[20][21][22][23][24] and higher BMI [24,25]. To our knowledge, no other studies reported a difference between leisure-time and work activity with regard to the fracture risk.…”
Section: Discussionmentioning
confidence: 52%
“…(19) A protective association of physical activity, often measured as leisure time activity in older studies, with hip fracture has been reported previously. (2)(3)(4)(5)(6)(7)(8)(9) One previous study has considered the potential competing effect of BMI with respect to the effects of walking and other leisure time activities on hip fracture risk. Total physical activity, made up of both leisure time and incidental physical activities, is increasingly recognized as a key determinant of disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Previous studies have reported a decreased risk of hip fracture among physically active women. (2)(3)(4)(5)(6)(7)(8)(9) Regular physical activity also has been associated with a lower risk of osteoporosis, obesity, (10) and falls. (11,12) The protective effect of physical activity on hip fracture has been attributed to increased forces on the bones that may slow the rate of decline in bone mineral density (BMD) related to aging (13,14) and/or prevent falls by improving balance, coordination, and muscular strength.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is important in the prevention of osteoporosis and osteoporosis-related fractures, and hip fractures generate the most morbidity and mortality and the highest costs (10,29) in the general population. Exercise has also been found to be important in reducing the risk of falling by improving balance and coordination (30).…”
Section: Discussionmentioning
confidence: 99%